Analisis Kompetensi Pustakawan dalam Mendukung Layanan Perpustakaan (Studi Kasus di Perpustakaan UIN Sunan Gunung Djati Bandung) - Hanany, L. Nailah Hanum (Institut Agama Islam Negeri (IAIN) Curup, 2023)
One of the determining factors in efforts to improve the quality of service in university libraries is to increase the competence of librarians. The digital era has changed the role of the library which has an impact on service changes. Accordingly, this study analyzes the competency of librarians in supporting library services at the Library of Islamic State of Sunan Gunung Djati Bandung using American Library Association (ALA) standards. The research approach uses descriptive qualitative with a case study model where researchers observe and examine documents and gather information by interviewing librarians, heads of libraries, heads of administration and staffing bureaus, and users consisting of lecturers and student. The results of the analysis show that the competence of librarians is still limited to managing printed collections. As for digital services, only 0.26% of the total number of librarians manage it so competencies related to digital library services need to be improved and developed.Â